Risk Assessment for Corneal Ectasia following Photorefractive Keratectomy - Nir Sorkin; Igor Kaiserman; Yuval Domniz; Tzahi Sela; Gur Munzer; David Varssano (Journal of Ophthalmology)
Purpose. To analyze the risk factors associated with a series of ectasia cases following photorefractive keratectomy (PRK) and all published cases. Methods. In a retrospective study on post-PRK ectasia patients, 9 eyes of 7 patients were included, in addition to 20 eyes of 13 patients from the literature. Risk of post-PRK ectasia was calculated using the ectasia risk score system (ERSS) for laser in situ keratomileusis (LASIK) patients. The percent tissue altered (PTA) was also evaluated. Results. ERSS scoring of zero for age, RSB, and spherical equivalent was found in 66%, 86%, and 86% of the eyes, respectively. Pachymetry risk score was 2 in 60% of the eyes and 3 or 4 in 16% of the eyes. Topography risk score was 3 in 41% of the eyes and 4 in 21% of the eyes. Cumulative ectasia risk score was ≥4 (high risk) in 77% of the eyes and ≥3 (medium and high risk) in 86% of the eyes. Average PTA was 23.2 ± 7.0%. All eyes but one had a PTA < 40%. Conclusions. Preoperative corneal topographic abnormalities and thin corneas may be significant risk factors for developing ectasia following PRK. Post-LASIK ectasia risk scoring also has relevance in the risk for developing post-PRK ectasia.